Project finance w inwestycjach infrastrukturalnych - Wojewnik-Filipkowska, Anna (Project Finance in Infrastructure Investment, 2006)
Municipal infrastructure service belongs to community duties in Poland. The object of consideration of this article is a situation when these community duties are fulfilled by commercial bodies and by special purpose vehicle companies. A special purpose vehicle company is characteristic of project finance. Project finance is a changing concept. It is not the only solution of carrying out infrastructure projects, however, it can be a preferable solution in certain circumstances, though, project finance application should be thought over and adjusted for features of a certain project. All strengths and weaknesses of any project finance structure and targets and purposes of all equal project participants should be accepted to guarantee the benefits and advantages of project finance. The article presents an attempt of classification of different manner application of project finance method in infrastructural investments
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 704-715